Peningkatan Kualitas Sinyal 4G Berdasarkan Nilai KPI Dengan Metode Drivetest Cluster Padang - Sri Yusnita; Yoga Saputra; Dikky Chandra; Popy Maria (Teknik Elektro Politeknik Negeri Padang, 2019)
The real signal quality measurement on the 4G network is a reference to improve signal quality. Measurements were made for two different operators on the Padang cluster. The measurement parameters taken are the RSRP value, SINR and throughput as the basic parameters of the KPI (Key Performance Indicator) standard. Measurement of these basic parameters is done by the drive test method using the Tems Pocket device while for data analysis using Tems discovery and Mapinfo Pro. Planning the data collection path is an important part to find out the bad spot areas of the two operators for planning signal quality improvement. The measurement results in the process of collecting data for bad categories and not being detected at all are used to determine the position of the new site by taking into account the three signal parameters, the number of users in the area, the minimum limit of the bad signal radius and the site positions that already exist for both operators. Using the cross method, three new site coordinate points are obtained, namely first at longitude 100.403428 ° and latitude -0.870309 °, second point at longitude 100.376331 ° and latitude -0.858726 °, and third point at longitude 100.404072 ° and latitude -0.966503 ° and 47 bad spot area.